Analysis of alkaloids in fermented and nonfermented blue lupin (L. angustifolius) products - Karath, Lakshmi (My University, 2024)
L. angustifolius, also known as blue lupin or sweet lupin belongs to the genus Lupinus, a member of the legume family Fabaceae. Lupins contain high amounts of protein, and some have high alkaloid content. Blue lupins contain antinutrients termed quinolizidine alkaloids which cause toxic effects on oral consumption. Blue lupins are utilized as a whole grain or ingredient in various food products. Therefore, analyzing alkaloids in blue lupin products has become necessary since quinolizidine alkaloid content in blue lupin products must be quantified before marketing as a final product. The study aimed to analyze quinolizidine alkaloids such as angustifoline, alpha-isolupanine, lupanine, sparteine, and 13-hydroxylupaninein in commercial lupin flour, 4 nonfermented and 11 fermented, (L. angustifolius) lupin milk samples. The lupin milk samples were fermented using different lactic acid bacteria (LAB) starters with or without a thickening agent. The sample pretreatment method was optimized and after extraction, the samples were analyzed using gas chromatography with a flame ionization detector. The total alkaloid content in nonfermented blue lupin milk samples was observed to be lower than in fermented blue lupin milk samples. Nonfermented samples with a thickening agent showed lower total alkaloid content than those without. Notably, samples containing a thickening agent (barley starch, 4% w/v) fermented with Mix E; an in-house (Natural Resources Institute Finland) isolate, originating from the plant, exhibited a total alkaloid content lower than other fermented samples. This study also emphasizes the importance and need to use optimal sample pretreatment and analysis methods to reliably study the alkaloid content in blue lupin ingredients and products during product development.
Keywords: Keywords: blue lupins, fermentation, GC-FID, quinolizidine alkaloids